Empowerment of Housewives Through Golden Banana Jam Innovation as a Business Opportunity in Donosari Village - Lestari, Diana Yuli; Putri, Elsa Fransisca; Maharani, Reza Astika Dwi; Yuda, Chan Krisna Anggara; Ujiyani, Nungki Marlia; Widianto, Ghozi Ulumuddin; Lutfiana, Elisa; Azka, Iman Nur; Sayyaf, Raihan I’zaz; Rini, Anggraeni Dwi Puspa; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
This research aims to empower housewives in Donosari Village through an innovative business opportunity: "Golden Banana Jam". Donosari, located in Sruweng District, Kebumen Regency, Central Java, has a total population of 2,540 people, with most residents working as farmers or farm laborers. The village has abundant natural resources, including a large number of banana trees, but the utilization of bananas is still limited. Currently, most bananas are sold raw or processed into banana chips, which is considered an easier option by the community. Golden Banana Jam. Jam is made from mashed bananas, sugar, and other ingredients, cooked until it thickens. This processing method extends the shelf life of the product compared to fresh bananas, which have a relatively short shelf life. The goal is to increase the economic value of bananas, as processed products like jam have a higher selling price than fresh bananas. The initiative, led by students from the Universitas Muhammadiyah Purwokerto KKN program, involved a training session on August 8, 2025, for the Family Welfare and Empowerment Team (TP PKK) of Donosari Village. The training provided participants with new knowledge and skills, with the hope that this innovation will create new business opportunities and support the local economy. The participants were enthusiastic about the training and the new product. It is expected that the development of this product will boost the village’s economy and support the growth of local MSMEs.